Պաղեստինյան հիմնախնդրի ջրային ասպեկտը - Հարությունյան, Կարեն («Զանգակ - 97»)
As one of the core issues of Arab-Israeli conflict, the water factor largely conditions relations between Palestinians and Israelis. The aiticle discusses the importance of the Jordan River waters and the West Bank and Gaza Strip aquifers in the context of the Palestinian problem.
Keywords: Պատմություն; Ջրային ռեսուրսներ